Cognitive-behavioral changes in amyotrophic lateral sclerosis: Screening prevalence and impact on patients and caregivers. Issue 5 (17th August 2016) - Bock, Meredith; Duong, Y-Nhy; Kim, Anthony; Allen, Isabel; Murphy, Jennifer; Lomen-Hoerth, Catherine
Abstract: Our objective was to evaluate the association between cognitive-behavioral deficits and patient quality of life (QoL), caregiver burden, and disease stage in a population of patients with amyotrophic lateral sclerosis (ALS). We administered the ALS Cognitive-Behavioral Screen™ to 86 patients with ALS. Multiple regression was used to evaluate the association between cognitive or behavioral deficits and disease stage, patient QoL, and caregiver burden while controlling for clinically important variables. Of 86 participants enrolled, 53 (62%) had some degree of cognitive impairment, 32 (37%) were behaviorally impaired and four met both cognitive and behavioral screening criteria for frontotemporal dementia (FTD). The severity of cognitive-behavioral deficits was not associated with patient QoL. More pronounced cognitive deficits (beta = –1.4, p  = 0.04) and behavioral symptoms (–0.69, p  < 0.001) predicted higher caregiver burden. Self-reported QoL was lower in patients with more depressive symptoms (beta = –0.32, p  < 0.001) and more advanced disease (beta =0.10, p  = 0.01). In conclusion, general QoL for patients with ALS is not associated with cognitive or behavioral deficits. More severe cognitive deficits and caregiver-reported behavioral symptoms predict higher caregiver burden. Routine cognitive-behavioral screening can identify patients who require full neuropsychological examination, inform patient counseling, and identify caregivers in need of early, targeted interventions.